Efektivitas Program Pendidikan Berbasis Komunitas dalam Meningkatkan Kesadaran Sosial di Karang Taruna Joyotakan - Abdurrahman, Mukhsin; Indarto, Pungki; Nurhidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of Karang Taruna Joyotakan in enhancing members’ social awareness through community-based education programs. The research employed a qualitative method with a case study approach. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that activities such as thematic discussions, skills training, and social actions successfully increased youths’ knowledge, empathy, sense of responsibility, and social engagement. This success was supported by active member participation and local partnership support. However, limited resources and members’ time dynamics remain challenges to the program’s sustainability. This study affirms that Karang Taruna can serve as a strategic agent in fostering social awareness among young generations, provided that programs are designed in a participatory manner and adapt to community.